Effects of continuous positive airway pressure treatment in obstructive sleep apnea patients with atrial fibrillation: A meta-analysis. Issue 15 (16th April 2021) - Li, Xinyao; Zhou, Xinbin; Xu, Xiaoming; Dai, Jin; Chen, Chen; Ma, Lan; Li, Jiaying; Mao, Wei; Zhu, Min
Abstract: Background: Obstructive sleep apnea (OSA) is correlated with atrial fibrillation (AF). Over the past decade, there has been an increasing interest in the relationship between OSA with continuous positive airway pressure (CPAP) and progression or recurrence of AF. Methods: This investigation was an analysis of studies searched in the Cochrane Library, PubMed, EMBASE, EBSCO, OVID, and Web of Science databases from inception to July 2020 to evaluate the recurrence or progression of AF in CPAP users, CPAP nonusers, and patients without OSA. Results: Nine studies with 14, 812 patients were recruited. CPAP therapy reduced the risk of AF recurrence or progression by 63% in a random-effects model (24.8% vs 40.5%, risk ratio [RR] = 0.70, 95% confidence interval [CI] = 0.57–0.85, P = .035). Compared with non-OSA patients, AF recurrence or progression was much higher in CPAP nonusers (40.6% vs 21.1%, RR = 1.70, 95% CI = 1.19–2.43, P = .000). However, AF recurrence or progression in the CPAP group was similar to that in the non-OSA group (24.0% vs 21.1%, RR = 1.13, 95% CI = 0.87–1.47, P = .001). Begg correlation test and Egger regression test revealed no publication bias in this analysis. Conclusions: OSA is a salient factor in the progression or recurrence of AF. CPAP therapy for OSA may contribute to reduction of AF in patients for whom radiofrequency ablation or direct current cardioversion is not performed. Trial Registration: The protocol for this meta-analysis was registered on PROSPERO with a registration No. CRD42019135229. Abstract : Supplemental Digital Content is available in the text